Micro‐endoscopy of the human vas deferens: a feasibility study of a novel device in several ex vivo models. (17th November 2016) - Trottmann, M.; Sroka, R.; Braun, C.; Liedl, B.; Schaaf, H.; Graw, M.; Becker, A. J.; Stief, C. G.; Khoder, W. Y.
Summary: The aim of this study was to show limitation as well as potential of micro‐endoscopy techniques as an innovative diagnostic and therapeutic approach in andrology. Two kinds of custom‐made micro‐endoscopes (ME) were tested in ex vivo vas deferens specimen and in post‐mortem whole body. The semi‐rigid ME included a micro‐optic (0.9 mm outer diameter [OD], 10.000 pixels, 120° vision angle [VE], 3–20 mm field depth [FD]) and an integrated fibre‐optic light source. The flexible ME was composed of a micro‐optic (OD = 0.6 mm, 6.000 pixels, 120° VE, 3–20 mm FD). The ex vivo study included retrograde investigation of the vas deferens (surgical specimen n = 9, radical prostatectomy n = 3). The post‐mortem investigation ( n = 4) included the inspection of the vas deferens via both approaches. The results showed that antegrade and retrograde rigid endoscopy of the vas deferens were achieved as a diagnostic tool. The working channel enabled therapeutic use including biopsies or baskets. Using the flexible ME, the orifices of the ejaculatory ducts were identified. In vivo cadaveric retrograde cannulation of the orifices was successful. Post‐mortem changes of verumontanum hindered the examinations beyond. Orifices were identified shaded behind a thin transparent membrane. Antegrade vasoscopy using flexible ME was possible up to the internal inguinal ring. Further advancement was impossible because of anatomical angle and lack adequate vision guidance. The vas deferens interior was clearly visible and was documented by pictures and movies. Altogether, the described ME techniques were feasible and effective, offering the potential of innovative diagnostic and therapeutic approaches for use in the genital tract. Several innovative indications could be expected.